The calculation of the thermodynamical properties in the liquid-gas region - Avsec, Jurij (Acta chimica slovenica, 1999)
The paper features the mathematical model of computing phase diagrams and thermodynamic functions of the state in the liquid, gas and two phase domain with the help of statistical thermodynamics. The paper features all important contributions (translation, rotation, internal rotation, vibration, intermolecular potential energy and influenceof electron and nuclei excitation). To calculate the thermodynamic properties of real gases we developed the cluster theory, which yields better results than the classical virial equation. For the realm of real liquids the Johnson-Zollweg-Gubbins model basedon the modified Benedict-Webb-Rubin eqution was applied. The Lennard-Jones intermolecular was used. The analytical resulats are compared with the thermodynamical data and models obtained by classical thermodynamics and show relatively good agreement.
Keywords: kapljevine; plini; termodinamične lastnosti; termodinamika